The Genetics and Biochemistry of Cell Wall Structure and Synthesis in Neurospora crassa, a Model Filamentous Fungus - Patel, Pavan K.; Free, Stephen J. (Frontiers in Microbiology, 2019)
This review discusses the wealth of information available for the N. crassa cell wall. The basic organization and structure of the cell wall is presented and how the wall changes during the N. crassa life cycle is discussed. Over forty cell wall glycoproteins have been identified by proteomic analyses. Genetic and biochemical studies have identified many of the key enzymes needed for cell wall biogenesis, and the roles these enzymes play in cell wall biogenesis are discussed. The review includes a discussion of how the major cell wall components (chitin, β-1,3-glucan, mixed β-1,3-/β-1,4- glucans, glycoproteins, and melanin) are synthesized and incorporated into the cell wall. We present a four-step model for how cell wall glycoproteins are covalently incorporated into the cell wall. In N. crassa, the covalent incorporation of cell wall glycoproteins into the wall occurs through a glycosidic linkage between lichenin (a mixed β-1,3-/β-1,4- glucan) and a “processed” galactomannan that has been attached to the glycoprotein N-linked oligosaccharides. The first step is the addition of the galactomannan to the N-linked oligosaccharide. Mutants affected in galactomannan formation are unable to incorporate glycoproteins into their cell walls. The second step is carried out by the enzymes from the GH76 family of α-1,6-mannanases, which cleave the galactomannan to generate a processed galactomannan. The model suggests that the third and fourth steps are carried out by members of the GH72 family of glucanosyltransferases. In the third step the glucanosyltransferases cleave lichenin and generate enzyme/substrate intermediates in which the lichenin is covalently attached to the active site of the glucanosyltransferases. In the final step, the glucanosyltransferases attach the lichenin onto the processed galactomannans, which creates new glycosidic bonds and effectively incorporates the glycoproteins into the cross-linked cell wall glucan/chitin matrix.